2013
DOI: 10.1007/s11657-012-0116-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of osteoporosis in otherwise healthy Indian males aged 50 years and above

Abstract: The osteoporosis affects 8.5 % of otherwise healthy males aged 50 years and above. Vitamin D deficiency is common in such group and maybe responsible for osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…Howe ver, the prevalence of VDD in Indian men is also quite high. For example, a study from Varanasi involving only men showed the prevalence of VDD to b e 58% 14 . In our study, 75% of the male subjects had either VDD or insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Howe ver, the prevalence of VDD in Indian men is also quite high. For example, a study from Varanasi involving only men showed the prevalence of VDD to b e 58% 14 . In our study, 75% of the male subjects had either VDD or insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…10 Similar study by Agarwal et al found 58% vitamin D deficiency incidence rate in their study group (composed of elderly of >50 yrs). 11 Correlation of vitamin D levels with BMD was found to be statistically very significant (p value=0.000). 70.58% osteoporotic subjects were vitamin D deficient.…”
Section: Discussionmentioning
confidence: 86%
“…9,10 However, in another study at Rochester, a 19%prevalence of osteoporosis has been reported, the differences in the prevalence that was seen between south Indian and north Indian subjects would have been due to many factors like genetic, nutritional, and other environmental factor which need to be looked at in further prospective studies. 11 The most dreaded complication of osteoporosis is hip fracture, which has been reported to be more in men when compared to women.…”
Section: Discussionmentioning
confidence: 93%